A Free-Flow Speed Model based on Portuguese Roadway Design Features for Two-Lane Highways - António Lobo (2013)
Speed is a key performance measure in economic and environrnental analyses of two-lane highways. Speed, combined with the percentage of time spent following, is also used in the assessment of levei of service. Under free-ftow conditions, the circulation of a given vehicle is not constrained by the presence of other vehicles, and the driver's speed choice reftects the driver's response to the geometric features of the road and roadside interference, as well as the driver's perception of risk. Many studies concerned with the effects of road characteristics, design features in particular, on vehicle speed have been conducted in several countries in recent decades. These studies have provided useful tools for modeling speed and evaluating alignment consistency. This paper presents an exponential free-flow speed model, applicable to both curves and tangents, developed for two-lane highways in Portugal. The variables included in the model are representative not only of the road element under consideration (curve or tangent) but also of the preceding road section and of the visual field downstream from the elemento The results from this model are compared with other authors' results and with the guidelines in the Highway Capacity Manua120LO. In addition to the primary inftuence of the horizontal curvature on speed, the results show that other factors, such as the cross-sectional width, the density of access points, and the downstream visibility, are important.